Pengaruh Bahan Karet Ban Bekas/Karet Alam (Hevea Brasiliensis) dan Polypropilena dalam Matriks Termoplastik - Adiansyah, Adiansyah; Hotromasari Dabukke; Salomo Sijabat; Berkat Panjaitan; Alfonso Butarbutar; Agusniat Zendrato; Ahmad Rizki Ananda Hasibuan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Research has been carried out on the influence of used tire rubber/natural rubber (Hevea Brasiliensis) and polypropylene in thermoplastic matrices. Natural rubber has clay properties, and is difficult to mix with other materials without a thermal process. This research was carried out using a heat process to speed up the mixing process. The aim of this research is to determine the effect of used tire rubber/natural rubber (Hevea Brasiliensis) and polypropylene in thermoplastic matrices. This research was carried out using varying concentrations of 25; 30; and 35 parts per hundred rubber (phr), while the initiator used is benzoyl peroxide as the initiator with variations of 0; 1.5; 1.9; 2.3 and 2.7. The research results concluded that the higher the phr, the lower the viscosity of the rubber compound, but the physical properties were not affected.